Effectiveness of deep breathing relaxation technique education on blood pressure reduction in hypertensive patients - Abubakar Betan; Lilis Lilis; Hendrik Hendrik (Journal Interdisciplinary Health, 2025)
Introduction: Hypertension is a significant non-communicable disease that remains a public health concern in Indonesia, especially in urban areas like Makassar. Pharmacological treatment often faces adherence challenges due to side effects and economic limitations. Non-pharmacological interventions such as deep breathing relaxation techniques offer a simple, low-cost, and effective alternative to manage blood pressure. This study aimed to analyze the effectiveness of educational interventions on deep breathing relaxation techniques in reducing blood pressure among hypertensive patients at Tamalanrea Jaya Public Health Center, Makassar. Methods: This case study used a descriptive design involving two female hypertensive patients aged 59 and 60. The intervention consisted of deep breathing relaxation therapy administered over three days, accompanied by structured health education on proper breathing techniques. Blood pressure was measured before and after each session. Results: Before the intervention, respondent 1 had a blood pressure of 160/120 mmHg, and respondent 2 had 170/120 mmHg. After three sessions of deep breathing relaxation, their blood pressure reduced to 130/90 mmHg and 140/90 mmHg, respectively. Both respondents reported improved comfort, relaxation, and adherence due to the simplicity and flexibility of the technique. Conclusion: The results indicate that deep breathing relaxation techniques, combined with structured education, effectively lower blood pressure in hypertensive patients. This method is practical, non-invasive, and can be performed independently at home. It is recommended as a complementary approach in primary health care settings to help manage hypertension and reduce the risk of complications